HUBUNGAN PEMERINTAH PUSAT DAN DAERAH DALAM PEMBANGUNAN INFRASTRUKTUR JALAN DI KOTA TANGERANG - Wulandari, Tri Ayu; Amelia, Mega; Suryani, Devina Ratna (Gapenas Publisher, 2025)
This study aims to analyze the relationship between the central government and local governments in the development of road infrastructure in Tangerang City. Road construction is one of the main factors in improving regional connectivity, smoothing the flow of goods and services, and supporting local economic growth. This research uses a qualitative descriptive method by analyzing various policy documents and government reports. The results of the study show that the relationship between the central and regional governments is running quite well through mutual financing mechanisms, technical coordination, and project implementation. However, there are still obstacles such as delays in funds, coordination between agencies, and differences in priorities between the central and regional governments.